Features of installing the Moodle 4.1 distance learning system on the Debian 11 operating system - Khou B., Maistrenko A. V. (Modern education development: theory, techniques and practice, 2023)
the problem of implementing distance learning forms using a common educational platform of the current version is considered. The sequence of installation, configuration and performance testing of the Moodle system on the Linux operating system is described.
Keywords: дистанционное обучение; программное обеспечение; электронные ресурсы; операционная система; база данных; установка; браузер; Distance learning; сервер; installation; electronic resources; software; database; server; образовательные платформы; настройка; educational platforms; configuration; operating system; browser